Silviculture as a tool for restoration of temperate forests - Bannister, Jan R; Donoso, Pablo J; Mujica, Rodrigo (BOSQUE, 2017)
When we apply silviculture in the context of forest restoration, we aim at increasing the biodiversity and structural complexity of degraded and fire-disturbed old-growth forests, secondary forests (degraded and with normal density) and exotic monocultures, in order to improve their ecological functionality and maximize the ecosystem services that they provide. This work aims at: a) providing a conceptual framework on the terminology related to forest restoration; b) highlighting the importance of silviculture as a tool for the restoration of forests; and c) recommending some basic questions that help professionals and technicians linked to forest restoration, to dimension the required efforts to apply restoration. Forest restoration in Chile should be based on a pragmatic and functional paradigm that includes a wide range of options or strategies dealing with transformed or degraded forest ecosystems, including ecological restoration, rehabilitation, reconstruction, replacement and conversion. Depending on the initial state in which the ecosystem is and the target state, some of these options will lead the ecosystem back to its historical state and others only will seek to restore some attributes. In this context, silviculture is the key to enrich the concepts of forest restoration, translating these into strategies, techniques and real practical solutions.